ISLAMIC EDUCATION FOR COMMUNITY OF COASTAL SOUTH JAVA (a Case Study of Coastal South Regency in Purworejo, Central Java) - Kasinu, Akhmad; Rokhmawanto, Sulis (Jurnal Pendidikan Islam, 2016)
Education is a mean of change in society for a better life. In the community, education process is conducted by religious leaders (scholars or clerics) and also institute religious organizations. In running the educational process, religious leaders and organizations experience rejection in various forms both in words and actions. Community culture which is not in accordance with the Islamic values is a form of impious action in which it is as an object of Islamic education activity in the community. Some types of impious activities are by not respecting each other, not praying, and not fasting. This phenomenon makes scholars and religious organizations rush to perform their functions in Islamic education process, to cultivate the values of tolerances in various dimensions and mutual respect through a synthesis of religion and culture.